Izbrani kazalci obremenjenosti okolja pri študijah ranljivosti okolja - Cigale, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
One of the components of the environmental vulnerability studies is also the evaluation of the pollution of the environment. In the article, the analysis of the selected indicators of the achieved degree of the total and integral pollution is presented. In the framework of the environmental vulnerability studies on the spatial level of landscape-ecological types for this purpose the following indicators were selected: population density, density of working places, traffic intensity and percentage of forests.
Keywords: ecology; ekologija; ekološko ravnotežje; environmental protection; onesnaževanje okolja; Slovenia; Slovenija; sonaravni razvoj; varstvo okolja